(untitled) (Research, Society and Development, 2020)
The objective was to identify the knowledge of the nursing team about cardiopulmonary arrest in the hospital environment. It is an integrative review that uses LILACS, SciELO, MEDLINE and SCOPUS as databases. Articles in Portuguese or English, consistent with the theme, full texts and on-line from 2015 to 2020 were included. Duplicate papers or articles that did not correspond to the objectives of the proposed analysis were excluded. Using the descriptors "Heart Arrest", "Knowledge" and "nursing", in English and Portuguese. All studies demonstrate, by means of different methods, that there is a great deficiency of qualifications and training on the subject in the environments in which they work, consequently the knowledge of these professionals becomes weakened. In a hospital in northeastern Brazil, with 101 professionals, it was found that 81.8% recognized the classic signs of a CRP and 80% knew the correct sequence of the important link. However, in another study it is possible to observe that 13.05% of nurses and 41.02% of nursing technicians, did not identify shockable heart rhythms. In relation to Advanced Life Support, only 17.39% of higher education professionals and 1.28% of technicians responded correctly. It was evident, through this study, that the deficient theoretical-practical knowledge about Cardiorespiratory Resuscitation, among the professionals of the nursing team, is deficient, making training and permanent education imperative, so that these professionals can offer better assistance in this type of occurrence.